Profiling inflammatory markers during the competitive season and post season in collegiate wrestlers - Roth, J.; Szczygiel, T.; Moore, M.; O'Connor, P.; Edwards, J.; Sharma, N.; Pettit-Mee, R.; Zuhl, M. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to determine whether biological markers of muscle damage and inflammation coincide with subjective measures of muscle fatigue and sleep quality among Division I collegiate wrestlers. The goal was to provide practitioners with noninvasive techniques to evaluate a wrestler's inflammatory state. Subjects from the Central Michigan University Division I collegiate wrestling team (n = 6) were analyzed on 6 separate occasions throughout the course of the competitive season and post season. Biological measurements (creatine kinase [CK], interleukin [IL]-6, tumor necrosis factor alpha [TNF-a], IL-1ß, IL-10) and subjective measurements (fatigue, muscle soreness, and sleep quality) were performed. The self-reported level of muscle soreness and fatigue was significantly higher from preseason through midseason, but leveled off late into the season. Creatine kinase followed a similar pattern early into the season compared with preseason and decreased at the end of season. Plasma TNF-a and IL-8 levels increased modestly late into season compared with preseason. Sleep quality correlated with plasma levels of IL-8 (r2 = 0.120, p < 0.05). Subjects experienced muscle soreness and fatigue early in the competitive season, along with an increase in markers of muscle damage. This may indicate an adaptive response to the training load. Low-grade systemic inflammation increased late into the season, and correlated with poor sleep quality. Based on these data, wrestlers may benefit by additional recovery time early into the season to prevent muscle fatigue and damage. As the season progresses, low-grade inflammation may be prevented or monitored by tracking the quality of sleep.